2018
DOI: 10.21109/kesmas.v13i1.1617
|View full text |Cite
|
Sign up to set email alerts
|

Direct Interaction with Cervical Cancer Patient, Husband Support and Self Perceived as Determinant Factors on Women’s Desire for Screening VIA test

Abstract: Cervical cancer causes 10.3% women mortality in Indonesia. Visual Inspection of Acetic Acid (VIA) had been used for screening program since 2014, but only 2.45% women took the test in 2015. In the place of this study, the coverage was at less than 1%. Previous studies revealed that psychosocial was an important factor, but less studies analyzed the role of husband support and direct experience with cervical cancer patient. The aim of the study was to learn correlation between direct experience with cervical ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…These findings imply that in terms of education about cervical cancer prevention for the Indonesian population, the target should not only be sexually active women but also their spouses or partners. Several studies support our findings and explain that knowledge, 11–15 spousal support, 16–21 and access to information 21–23 substantially influence the willingness to undergo cervical cancer among sexually active women.…”
Section: Discussionsupporting
confidence: 86%
“…These findings imply that in terms of education about cervical cancer prevention for the Indonesian population, the target should not only be sexually active women but also their spouses or partners. Several studies support our findings and explain that knowledge, 11–15 spousal support, 16–21 and access to information 21–23 substantially influence the willingness to undergo cervical cancer among sexually active women.…”
Section: Discussionsupporting
confidence: 86%
“…Two studies reported pap smears for CCS [ 72 , 73 ], while two studies reported both pap smear and VIA [ 81 , 82 ]. The prevalence of having a screening done in the past ranged from 5.5% to 33.3% [ 71 , 72 , 73 , 76 , 80 , 81 , 85 ], while participants’ desire to screen was 45.2% and 57.4% based on two studies [ 77 , 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…A majority of the studies (n = 81) were crosssectional or case-control studies, while the rest were qualitative (n = 9) or mixed-methods (n = 3) studies. Most of the studies were conducted in Malaysia (35.5%, n = 33) , followed by Thailand (24.7%, n = 23) , Indonesia (16.1%, n = 15) [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85], and Singapore (15.1%, n = 14) [86][87][88][89][90][91][92][93][94][95][96][97][98][99]. None of the studies were conducted in the Philippines and Timor-Leste.…”
Section: Study Characteristicsmentioning
confidence: 99%